Content and Language Integrated Learning in Bilingual Education: : What Can We Learn from the Previous Studies? - Kadek Nila Hendra Yani; I Gede Budasi; Dewa Putu Ramendra; Luh Putu Artini; I Ketut Trika Adi Ana (Journey: Journal of English Language and Pedagogy, 2023)
CLIL is widely implemented in English as a foreign language class, but there has been no specific research conducted to identify the advantages and challenges of implementing it in the context of bilingual education. This study aims to examine the implementation of Content and Language Integrated Learning (CLIL) in bilingual education. Specifically, this study focuses on the benefits of CLIL in bilingual education and the challenges of implementing CLIL in bilingual education. Then, a recommendation to implement CLIL effectively was drawn using the benefits and the challenges of CLIL. This research was conducted by following the steps of a literature review. Data was collected from articles from accredited international journals published online from 2012 to 2022. The collected data were analyzed qualitatively using an interactive data analysis model, carried out in three stages of analysis: data reduction, data display, and conclusion drawing/verification. The data collected showed that CLIL improved mastery of a second language. It is because CLIL provides a lot of exposure for the students. Besides, CLIL enables students to acquire English by practicing it actively. The challenge in implementing CLIL lies in teachers’, students’, and teaching media readiness. To run CLIL effectively, it should be done by considering the quality, quantity, and consistency of the English exposure.